Tertiary-Amine-Catalyzed Asymmetric [3+2] Annulations of Morita–Baylis–Hillman Carbonates of Isatins with Nitroolefins to Construct Spirooxindoles - Peng, Jing; Ran, Guang-Yao; Du, Wei; Chen, Ying-Chun (Synthesis, 2015)
An enantioselective [3+2] annulation of nitroolefins with racemic Morita–Baylis–Hillman carbonates of isatins catalyzed by α-isocupreine has been developed. Chiral spirocyclic 2-oxindoles bearing an unusual cyclopentadiene motif were produced in excellent enantioselectivity (up to 98% ee) after the tandem elimination of HNO2 in the presence of DIPEA.
Keywords: Morita–Baylis–Hillman carbonates; asymmetric [3+2] annulation; spirooxindole; cyclopentadiene